2019
DOI: 10.14710/lr.v15i1.23357
|View full text |Cite
|
Sign up to set email alerts
|

Optimalisasi Peningkatan Kualitas Kredit Dalam Rangka Mengatasi Kredit Bermasalah

Abstract: Namun kredit juga merupakan kegiatan bisnis yang mempunyai risiko yang dapat berpengaruh pada tingkat kesehatan bank dan kelangsungan usaha bank. Untuk dapat mengoptimalkan kualitas kredit menjadi sebuah pekerjaan penting yang harus dilakukan. Sehingga diperlukan penyaluran kredit yang penuh ketelitian supaya menghasilkan kredit yang maksimal.Kredit yang diberikan PT.Bank Mandiri cabang Semarang mengalami tingkat angka kredit bermasalah atau Non Performing Loan (NPL) yang tergolong kurang sehat. Sehingga perlu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
11

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 0 publications
1
6
0
11
Order By: Relevance
“…Prospective customers who are known to have good behavior as village manners will be more considered in the loan approval process This is because BUMDes believes that customers who are local village manners feel that they belong to BUMDes, so they will be more appreciate their obligations in paying installments for the sustainability of the BUMDes. These findings support previous research that (Chosyali & Sartono, 2019) found that decisions in the settlement of bad loans will be better when internal control systems, especially in lending, are effectively implemented. BUMDes, which implements an internal control system for providing credit adequately, will help the board maintain its assets because the risk of the onset of bad loans can be suppressed.…”
Section: Discussion the Effects Of Internal Control System On Bad Loasupporting
confidence: 90%
“…Prospective customers who are known to have good behavior as village manners will be more considered in the loan approval process This is because BUMDes believes that customers who are local village manners feel that they belong to BUMDes, so they will be more appreciate their obligations in paying installments for the sustainability of the BUMDes. These findings support previous research that (Chosyali & Sartono, 2019) found that decisions in the settlement of bad loans will be better when internal control systems, especially in lending, are effectively implemented. BUMDes, which implements an internal control system for providing credit adequately, will help the board maintain its assets because the risk of the onset of bad loans can be suppressed.…”
Section: Discussion the Effects Of Internal Control System On Bad Loasupporting
confidence: 90%
“…BRI Unit Pasar Boyolali Office. The empirical approach in this study was conducted with the aim of obtaining empirical knowledge so as to facilitate the authors in concluding (Chosyali & Sartono, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Banking as a financial services industry in Indonesia, is an industry that plays an important role in economic activities (Cvijovic, Stankovic, & Relljic, 2017). Banking also has a role in efforts to improve people's welfare by supporting the implementation of national development (Chosyali & Sartono, 2019). The large variety of services offered by different banks causes the level of competition to be high, especially to obtain customers.…”
Section: Introductionmentioning
confidence: 99%
“…Kredit macet dapat disebabkan oleh berbagai faktor, baik faktor internal maupun eksternal (Chosyali & Sartono, 2019). Faktor internal meliputi karakter nasabah (character) yaitu itikad baik dari nasabah untuk membayar pinjamannya, faktor nasabah yang tidak mampu mengelola usahanya (capacity), dan nasabah menyalahgunakan kredit yang diperolehnya (capital).…”
Section: Penyelesaian Kredit Macet Melalui Penghapusbukuanunclassified